Ghosting on Tinder: Examining Disconnectivity in Online Dating - Anamarija Šiša (Media and Communication)
This study examines the phenomenon of ghosting on the mobile dating app Tinder among Slovenia’s dating app users. Ghosting is defined as the unexpected unilateral termination of communication in interpersonal relationships exerted through digital platforms. Drawing upon data from the walkthrough of the mobile dating app Tinder and 26 semi-structured interviews with users living in Ljubljana (Slovenia), ghosting is conceptualized as an undesirable but normalized disconnection strategy on Tinder. We argue that choosing ghosting as a communication strategy emerges predominantly from two different contexts. Firstly, from the need to protect oneself from harassment and vulnerability, and secondly, as a reaction to the information overload in an environment that demands perpetual activity, availability, and interaction. Therefore, it manifests as a disconnection strategy on an interaction level or as a consequence of disconnecting from the platform itself. According to users, the desire to disconnect from others and exit the app is as high and ambiguous as the desire to connect and experience an ego boost or the excitement of interactions. Ghosting on Tinder, therefore, emerges as a response to general hyperconnectivity to navigate the increasing information overload and to a feeling of loss of the possibilities for safe and authentic connections in digital spaces.